Meretas pemikiran strategik : pemecahan masalah di Indonesia melalui teropong ekonomi politik psikologi - Afiff, Faisal; Wiadi, Iyus, 1965- (Bandung : Refika Aditama, 2011)
Strategic thoughts for socioeconomic problems in Indonesia from economical, political, and psychological perspectives.
Includes bibliographical references (p. 213-216).